Sarothamnus scoparius (L.) W.D.J. Koch — indicator of global warming - Melnyk, V.I.; Baransky, А.R. (Reports of the National Academy of Sciences of Ukraine, 2018)
The genesis of the area of sub-Atlantic species Sarothamnus scoparius in the Eastern Europe is analyzed. It is shown that, in the XIX century, the species was not part of the natural flora of the Eastern Europe, but only grown in culture. From the cultivation areas, Sarothamnus scoparius has penetrated into natural ecosystems. In the second half of the XX century, the rate of migration of the species to the east significantly increases due to the warming of the climate and intense anthropogenic changes in the natural environment. The analysis of the geographical distribution and habitats of S. scoparius in the historical aspect has shown that this species is kenophyte and ergasiophyte of the Ukrainian flora. It has been established that S. scoparius is a sensitive indicator of the warming, and its populations can be convenient models for monitoring the vegetation changes due to climatic changes.